Construction and Validation of the Belief in Divine Retribution Scale for Pakistani Muslims - Naeem, Taram (Journal of religion and health, 2024)
The purpose of the study was to construct and validate a Belief in Divine Retribution Scale for the Pakistani Muslim population. The process of construction and validation was completed by following standardized guidelines for scale construction (Boateng et al., 2018). The present study was carried out in four phases. In phase I, the task of item generation was completed through literature review and interviews (inductive and deductive approaches). Phase II aimed at exploration of factor structure. Exploratory factor analysis was carried out on a sample of seven hundred Muslim participants. Data for EFA were collected through a purposive sampling technique, which comprised both men (n = 339) and women (n = 361) with an age range of 18 to 69 years. Results of EFA revealed a two-factor structure with a cumulative variance of 42.59 and with a Cronbach alpha reliability of .83. To confirm the obtained factor structure, Phase III was carried out on a sample of three hundred Muslim participants. The results of CFA confirmed the two-dimensional factor structure with a good model fit to the data. Phase IV provided evidence of convergent and discriminant validity of the scale. Moreover, data for validation were collected from an independent sample (N = 204). Finally, the results of validation revealed that there exists a significant positive correlation of Belief in Divine Retribution Scale with Belief in Just World Scale, which provided evidence of convergent validity. However, there exists a non-significant correlation of Belief in Divine Retribution Scale with Religious Practice Subscale of Short Muslim Practice and Belief Scale, and it provided evidence of discriminant validity. Implications along with limitations and suggestions for future research have also been mentioned.